EXPLORING THE PERCEPTION OF IIUM STUDENTS TOWARDS THE CONCEPT OF SOCIAL SOLIDARITY IN MULTICULTURAL MUSLIM STUDENTS: A PHENOMENOLOGICAL STUDY - Nor Athiah Mohd Noor; Suhailah Hussien, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
IIUM, as an Islamic institution of higher education, aspires to be a centre of educational excellence that emphasizes Islamic values and internationalization. It is reflected in its vision and mission that embraces the Ummatic concept. In an attempt to examine students’ experiences of IIUM in this respect, the study explores the perceptions of IIUM Muslim students of the concept of social solidarity in the multicultural Muslim community through their experience studying at IIUM. The study employed the phenomenological research design, where ten participants were selected using purposive sampling. The data were then analyzed using thematic analysis. Research findings of the study showed that participants perceive social solidarity at IIUM through the themes of collective commitment and spiritual motivation. It emphasizes the need to improve the curriculum, co-curriculum, and learning environment that considers the multicultural background of the students. The study reveals the need for educators and university management to work together to develop curriculum, teaching and learning, and management practices that promote social solidarity among multicultural students in Islamic universities such as IIUM